Salsa World : A Global Dance in Local Contexts - Hutchinson, Sydney, 1975- (Book collections on Project MUSE., 2014)
Since its emergence in the 1960s, salsa has transformed from a symbol of Nuyorican pride into an emblem of pan-Latinism and finally a form of global popular culture. While Latinos all over the world have developed and even exported their own "dance accents," local dance scenes have arisen in increasingly far-flung locations, each with their own flavor and unique features. This book examines the ways in which bodies relate to culture in specific places. The contributors, a notable group of scholars and practitioners, analyze dance practices in the U.S., Japan, Spain, France, Colombia, Cuba, Puerto Rico, and the Dominican Republic. Writing from the disciplines of ethnomusicology, anthropology, sociology, and performance studies, the contributors explore salsa's kinetopias - places defined by movement, or vice versa - as they have arisen through the dance's interaction with local histories, identities, and musical forms. Taken together, the essays in this book examine contemporary salsa dancing in all its complexity, taking special note of how it is localized and how issues of geography, race and ethnicity, and identity interact with the global salsa industry. Contributors include Bárbara Balbuena Gutiérrez, Katherine Borland, Joanna Bosse, Rossy Díaz, Saúl Escalona, Kengo Iwanaga, Isabel Llano, Jonathan S. Marion, Priscilla Renta, Alejandro Ulloa Sanmiguel, and the editor.